About The Contact Lens Sensor Triggerfish®: Experiences Up Until Now: O kontaktni leči Sensor Triggerfish®: dosedanje izkušnje - Faschinger, Christoph; Faschinger, Eva; Krainz, Sarah; Mossböck, Georg (Acta Medico-Biotechnica, 2021)
The purpose is to describe the new device Triggerfish, a sensor contact lens for continuous intraocular pressure measurements, the experiences so far and to judge the possible necessity. Literature search and own publications are presented. Good tolerability and safety, good to fair reproducibility, no validity was observed. Up to now there are too less data to include this new device in every–day practice as a necessary tool for the management of glaucoma. Much more studies testing the validity are warranted.
Keywords: intraocular pressure; sensor contact lens; safety; tolerability; reproducibility; validity